Gender Differences in Psoriatic Arthritis With Fatigue, Pain, Function, and Work Disability. Issue 4 (October 2019) - Braaten, Tawnie J.; Zhang, Chong; Presson, Angela P.; Breviu, Brian; Clegg, Daniel; Walsh, Jessica A.
Introduction/Objectives: Gender is an important patient characteristic that may be used to predict clinical presentation, disease progression, and therapeutic response. In recent studies, women with psoriatic arthritis (PsA) have reported less favorable function, increased fatigue, and decreased quality of life, compared to men. Less is known about gender differences with other patient-reported outcomes (PROs) such as pain and work limitations. Our purpose was to characterize gender differences in PROs in participants of the Utah Psoriasis Initiative (UPI) Arthritis Registry. Methods: In this cross-sectional study, PROs assessing pain, fatigue, quality of life, and function were compared between men and women enrolled in the UPI Arthritis Registry between January 2010 and November 2014. Work limitations were assessed in the subset of participants working for pay at the time of enrollment. Results: Participants included 115 men and 138 women. Women had less favorable PROs for pain, fatigue, patient-reported joint count, physical demands at work, work output, and function, as measured by both Health Assessment Questionnaire and the Psoriatic Arthritis Screening and Evaluation function subscale. Conclusions: Women experienced PsA differently than men, with higher fatigue, pain, work disability, and functional limitations. The etiology of the gender differences in PsA are unclear, and further research is indicated to better understand the role of hormones, gene expression, and other potential pathophysiologic differences between men and women.